Multiple temporalities in cities: between historiography and the emergence of the urban space: Multiple temporalities in cities: between historiography and the emergence of the urban space (Revista de História da UEG (REVHIST), 2025)
This study analyzes urban space as a historical synthesis shaped by overlapping temporalities that encompass social practices, symbolic disputes, and ways of producing the urban experience. It articulates assumptions of architecture, urbanism, and human action, revealing dimensions that give rise to meanings, uses, and tensions within the urban landscape. It emphasizes the role of collective memory in the processes of preservation, erasure, and re-signification that permeate these spaces. Contemporary urbanization, marked by economic logic and accelerated dynamics, contributes to the weakening of public uses and democratic functions of the city. Ultimately, the study advocates critical interpretations and integrated policies capable of restoring the historical, social, and identity potential of urban spaces as places of memory, social interaction, and citizen participation.Keywords: Cities. History. Urbanism.